METHODOLOGY OF FUNCTIONAL-COST ANALYSIS SYSTEMS OF MANAGEMENT OF BODY SECURITY MILITARY UNITS - Pavlov, Serhii; Osipenko, Stanislav; Kizian, Ruslan (Honor and Law, 2022)
The possibility of applying the methodological provisions of the theory of functional-cost analysis (FСA) to justify directions for improving the efficiency of the rear support management system of the military unit is considered. FСA is defined as a method of studying system-type objects (products, services, processes, etc.) complex in terms of construction and connections with the internal and external environment with the aim of ensuring the compliance of the functions of their structural elements with the general purpose of the objects, as well as the cost of resources for implementation these functions. The rear support management system of the military unit as an FСA object is represented as a set of organizationally and functionally separated structural units of the rear and includes the following components (subdivisions): rear management, food service, material service, fuel and lubricant service, housing and operation service and veterinary service (if available). To carry out the FСA of the rear support management system, a single list of functions has been defined for all its divisions: setting goals and objectives, planning, organization, motivation, accounting, control and analysis. Formulated tasks of the FСA of the rear support management system: based on the assessment of the results of the activities of the units of the rear support management system by its units and their functions, the costs of ensuring the activities of the units and the performance of functions, the effectiveness of management activities by units and functions is determined by comparing their contribution to the overall result of the rear operations and costs for their maintenance and implementation, a comparative analysis of efficiency is carried out in order to determine reserves for its improvement and develop measures for their implementation. The proposed scheme for solving the formulated problem, which includes six blocks: calculation of utility indicators by subdivisions and functions of the management system; cost calculation by divisions and functions of the management system; calculation of efficiency indicators by divisions and functions of the management system; analysis of performance indicators by divisions and functions of the management system; determination of reserves for increasing the efficiency of the management system; substantiation of measures to implement reserves, implementation, control, regulation. A scientific and methodological apparatus was formed for the implementation of the proposed scheme.